KNOWLEDGE, ATTITUDE AND RISK PERCEPTION OF COVID-19 AMONG NIGERIANS - Fadeyi , Abayomi; Adeoti , Adekunle Olatayo; Adeboye , Muhammed Akanbi Nurudeen; Awosanya, Joseph Abioye; Oluwadiya, Ibironke Omowumi; Oluwadiya, Kehinde Sunday (African Journal of Infectious Diseases (AJID), 2022)
Background: COVID-19 emerged as a novel disease with global health importance. Personal and collective behaviours have been modified to prevent the spread of this pandemic. This study is aimed to assess the knowledge, attitude and risk perceptions of Nigerians towards COVID-19. Method: A cross-sectional survey was conducted between the 30th of April and 17th of May 2020 with a national representative among Nigerians using a combination of online and interviewer administered questionnaire. Results: A total of 1,135 respondents participated in the study with a slight male preponderance (M: F=1.5:1). The mean age of the participants was 42±12.2 years with the majority (77%) between the ages of 26 and 55 years. The majority were aware of the pandemic, mostly through mass and social media. Most of the respondents demonstrated good knowledge of COVID-19 but the unaware minority (0.6%) were likewise uneducated. Educational status had no significant association with attitude towards hand washing and wearing of face mask (p>0.05). Risk perception was however low to moderate despite their concerns for COVID-19 and lack of trust in the governments’ response to the disease. Conclusion: The risk perception of COVID-19 among the respondents is not encouraging, hence more advocacy and public orientation must be done to curb further spread of COVID-19 in our setting.